An isolated‐boost‐converter‐based unidirectional three‐phase off‐board fast charger for electric vehicles - Ahmed Elserougi; Ibrahim Abdelsalam; Ahmed Massoud (IET Electrical Systems in Transportation)
Abstract In this work, a novel three‐phase unidirectional off‐board Electric Vehicles (EVs) fast charger is proposed. Each phase of the proposed converter consists of a two‐stage converter. The first stage is an AC–DC front‐end converter with power factor correction (PFC) control. The front‐end AC–DC converter is based on an isolated boost converter, which has a boosting capability and provides galvanic isolation. In this stage, parallel‐in parallel‐out isolated boost converter modules are employed in each phase. This enables sharing the current among modules to avoid implementing one module with a high current rating to meet the fast‐charging requirements. The multimodule option provides fault‐ride through capability for the proposed charger. The DC outputs of involved phases, that is, three isolated DC voltages, are fed to three cascaded DC–DC unidirectional buck converters. The charging terminals are used to charge the EV battery through a filter inductor with a charging current controller's aid. A detailed illustration of the suggested closed‐loop controllers is presented to ensure a successful operation for the proposed architecture. A simulation case study for a 25‐kW charger is presented. Finally, a 1‐kW prototype is implemented for experimental validation.